2015
DOI: 10.2147/jhl.s45077
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the implementation of evidence-based practice through contextual support and nursing leadership

Abstract: Background/purposeNurse managers (NMs) play an important role promoting evidence-based practice (EBP) on clinical units within hospitals. However, there is a dearth of research focused on NM perspectives about institutional contextual factors to support the goal of EBP on the clinical unit. The purpose of this article is to identify contextual factors described by NMs to drive change and facilitate EBP at the unit level, comparing and contrasting these perspectives across nursing units.MethodsThis study employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 17 publications
3
74
0
1
Order By: Relevance
“…, Kueny et al . ). The construct of absorptive capacity routines has been used to understand how health‐care organisations implement new practices (Berta & Baker , Berta et al .…”
Section: Aimsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Kueny et al . ). The construct of absorptive capacity routines has been used to understand how health‐care organisations implement new practices (Berta & Baker , Berta et al .…”
Section: Aimsmentioning
confidence: 97%
“…This framework highlights important absorptive capacity metaroutines and routines that nurse managers might put in place to support the identification, adoption, implementation, adaptation and replication of evidence-based practices. As leaders within healthcare organisations, nurse managers are ideally situated to use these routines to foster the adoption and use of new practices (Stetler 2004, Fleiszer et al 2015, Kueny et al 2015. Nurse managers can ensure that there are organisational members who are committed to scanning the environment for new ideas to improve patient care, as this has been shown to increase the ª 2016 John Wiley & Sons Ltd uptake of evidence-based practice (Panzano & Roth 2006, Berta et al 2010.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse managers clearly have a role in the implementation of new practices, processes, and activities in clinical settings and, as such, are the primary gatekeepers of EBP for the profession (Bleich & Kist, ; Fleiszer et al., ; Innis & Berta, ; Kueny, Titler, Mackin, & Shever, ; Stetler, Ritchie, Rycroft‐Malone, & Charns, ). They are often responsible for implementing new practices, processes, and activities in their organisations (Bleich & Kist, ; Fleiszer et al., ; Innis & Berta, ; Kueny et al., ; Stetler et al., ). To promote EBP, both leadership and facilitation interventions are needed (Dogherty, Harrison, & Graham, ; Fleiszer et al., ; Sandström, Borglin, Nilsson, & Willman, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of barriers have been identified that contribute to this gap, including unfavourable attitudes towards EBPs, inaccessibility to technology and computer systems, limited training on finding and implementing research knowledge and strained resources (Grimshaw, Eccles, Lavis, Hill, & Squires, ; Tacia, Biskupski, Pheley, & Lehto, ). Another important barrier is lack of awareness of the surrounding or contextual factors that may support or thwart efforts to implement and sustain EBPs (Kueny, Shever, Lehan Mackin, & Titler, ). Deeper understanding of these factors and their impact on the uptake of EBPs has become a major research focus for implementation science in the past decade (Eccles et al, ).…”
Section: Introductionmentioning
confidence: 99%